Trust in the Public Administration - Güemes, Cecilia (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The aims of this study are: (1) to highlight the importance of trust in the Public Administration; (2) to arrive at a definition and characterization of trust in the Public Administration; (3) to analyze the causes and factors that explain its presence/absence in certain societies; and (4) to systematize different proposals that are currently being debated with the objective of creating, rebuilding and/or recovering institutional trust.
Keywords: trust; Public Adminsitration; fair processes; outpout; social imaginaries